2013
DOI: 10.1186/1742-4690-10-59
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally-live attenuated SIV upregulates global T effector memory cell frequency under replication permissive conditions

Abstract: BackgroundLive attenuated SIV induces potent protection against superinfection with virulent virus; however the mechanism of this vaccine effect is poorly understood. Such knowledge is important for the development of clinically acceptable vaccine modalities against HIV.ResultsUsing a novel, doxycycline dependent, replication-competent live-attenuated SIVmac239Δnef (SIV-rtTAΔnef), we show that under replication-permissive conditions SIV-rtTAΔnef is fully viable. Twelve rhesus macaques were infected with a peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Total SIV gag vRNA profiles are shown for Groups A-C as a continuum of vaccination and wild-type challenge profiles (Fig 1C). As previously reported [26], the SIVrtTA vaccinates displayed a transient peak in plasma vRNA kinetics which is characteristic for attenuated SIVmac239Δ nef with two exceptions: E65 (Group A) and E70 (Group B). These animals exhibited a persisting shoulder of ~ 10 2 vRNA copies/ml to ~100 days post-vaccination.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Total SIV gag vRNA profiles are shown for Groups A-C as a continuum of vaccination and wild-type challenge profiles (Fig 1C). As previously reported [26], the SIVrtTA vaccinates displayed a transient peak in plasma vRNA kinetics which is characteristic for attenuated SIVmac239Δ nef with two exceptions: E65 (Group A) and E70 (Group B). These animals exhibited a persisting shoulder of ~ 10 2 vRNA copies/ml to ~100 days post-vaccination.…”
Section: Resultssupporting
confidence: 77%
“…We have previously reported that under replication permissive conditions, during the period when live attenuated virus RNA was essentially below the limit of detection in plasma, the global circulating T effector memory (T EM ) cell frequency was upregulated [26]. Hence, we were interested to determine if this effect was associated with the degree of protection from superinfection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies are exploring the links between immunity to HERV antigens, HERV antigen reactivation, and HIV and SIV infection, and preliminary experiments are showing strong correlates of protection using HERV antigen immunization to protect against SIV and HIV using a "cross-clade" immunogenicity approach (Jones et al, 2012). Other methodologies being explored include conditionally replicating SHIVs that can be "turned on" or "off" with antibiotics or other substrates that allow closer examinations of the effective immune responses associated with antigen persistence, yet better control of attenuated vaccines that may limit their potential for pathogenicity (Manoussaka et al, 2013).…”
Section: Future Directions For Siv Models For Hiv Researchmentioning
confidence: 99%